A Perspective on Training Methods Aimed at Building Local Capacity for the Assessment and Implementation of Environmental Flows in Rivers - O'Keeffe, Jeremy Howard (Frontiers in Environmental Science, 2018)
This paper describes the development and delivery of a global training programme for environmental flows in rivers. The programme was developed in South Africa, and formalised with WWF. It has been delivered at various levels of detail, to specialist teams of scientists and managers (as learning-by-doing), and to large numbers of post-graduate students, in more than 20 countries worldwide. The intention has been to build local capacity and initiate E flows implementation. The general format of the training is described, and a number of examples and case studies are used to demonstrate the successes and pitfalls of the process. The examples concentrate on the need for long-term commitment and persistence in the face of multiple impediments, chief among them the need to change mind-sets of water policy makers, managers, scientists, and all levels of stakeholders, who traditionally view rivers as resources to be used to the maximum extent, rather than as valuable assets to be protected. They also illustrate examples of misunderstanding and resistance to implementing E flows. Lessons from training and implementation over 25 years include: • The need for local champions, with a long-term commitment • The need for understanding and support from all levels of stakeholders • The need (at least initially) to simplify the process as much as possible, so as to foster understanding and support, and to demonstrate successes within a time frame that maintains that support.